Two-vehicle look-ahead convoy control systems - Sudin, Shahdan; Cook, Peter A. (IEEE, 2004)
The control system on each vehicle in a convoy requires information about the motion of preceding vehicles, in order to maintain stability and satisfy operating constraints. A two-vehicle look-ahead control strategy is proposed and investigated for the operation of a convoy, with the introduction of vehicle dynamics. Two control laws for this strategy are considered and compared. Simulation results illustrate the effect of the control strategy together with the vehicle dynamics and the response of the convoy to the presence of sudden short disturbances. They also show that the proposed control strategy can maintain string stability of the convoy system.